Dissociable spatial memory systems revealed by typical and atypical human development. Issue 2 (18th September 2018) - Julian, Joshua B.; Kamps, Frederik S.; Epstein, Russell A.; Dilks, Daniel D.
Abstract: Rodent lesion studies have revealed the existence of two causally dissociable spatial memory systems, localized to the hippocampus and striatum that are preferentially sensitive to environmental boundaries and landmark objects, respectively. Here we test whether these two memory systems are causally dissociable in humans by examining boundary‐ and landmark‐based memory in typical and atypical development. Adults with Williams syndrome (WS)—a developmental disorder with known hippocampal abnormalities—and typical children and adults, performed a navigation task that involved learning locations relative to a boundary or a landmark object. We found that boundary‐based memory was severely impaired in WS compared to typically‐developing mental‐age matched (MA) children and chronological‐age matched (CA) adults, whereas landmark‐based memory was similar in all groups. Furthermore, landmark‐based memory matured earlier in typical development than boundary‐based memory, consistent with the idea that the WS cognitive phenotype arises from developmental arrest of late maturing cognitive systems. Together, these findings provide causal and developmental evidence for dissociable spatial memory systems in humans. Abstract : Julian and colleagues used an established behavioral paradigm to examine boundary‐ and landmark‐based spatial memory systems in adults with Williams Syndrome and typically‐developing children and adults. The findings reveal causal and developmental evidence for dissociable spatial memory systems in humans.